Functional relationship of longitudinal and circular layers of the muscularis externa of the rabbit large intestine - McKirdy, H. C. (1972)
1. The functional relationship of the longitudinal and circular layers of the muscularis externa of the rabbit large intestine has been studied in a flat preparation. 2. Evidence is presented that mechanical activity can be recorded independently and simultaneously from the two muscle layers of the flat preparation. Such evidence accrues mainly from results obtained from the flat preparation in response to various drugs. 3. During spontaneous rhythmic contractions and during the response to pelvic (parasympathetic) nerve stimulation, both layers show similar activity, never opposite or reciprocal activity. 4. In this flat preparation, the mechanism controlling the level of sustained tension (i.e. `tone') may be dissociable, within limit, from the mechanism controlling rhythmic contractions.